2019
DOI: 10.4236/jtts.2019.93018
|View full text |Cite
|
Sign up to set email alerts
|

Measuring West-Africa Ports Efficiency Using Data Envelopment Analysis

Abstract: The present study measured the relative efficiency of five major commercial ports in West Africa, using three different Data Envelopment Analysis (DEA) methods, the CCR, BCC, and Windows I-C methods over the years 2005-2016. Seven input variables and one output variable were used in the model analysis. The CCR and BCC methods were used to evaluate the technical and scale efficiency while the Windows I-C method provided a comprehensive ranking of the studied ports. The results showed that the scale efficiency s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Several scholars have noted its significance in their studies. Among of them, Kalgora (2019) stated that seaport has to pursue service quality in order to remain at the top of the sector within its region, which later affects the improvement of a nation's economy [10]. A similar view was also reported by Bae and Park, 2018; Pham and Yeo, 2019 who argued that advancement of service quality is one way to gain a competitive edge in maritime transportation for the seaports [6,7].…”
Section: Applications Of Service Quality Model In the Seaportmentioning
confidence: 75%
See 1 more Smart Citation
“…Several scholars have noted its significance in their studies. Among of them, Kalgora (2019) stated that seaport has to pursue service quality in order to remain at the top of the sector within its region, which later affects the improvement of a nation's economy [10]. A similar view was also reported by Bae and Park, 2018; Pham and Yeo, 2019 who argued that advancement of service quality is one way to gain a competitive edge in maritime transportation for the seaports [6,7].…”
Section: Applications Of Service Quality Model In the Seaportmentioning
confidence: 75%
“…Expansion of seaport industry in this region suggested the seaport authority to shift the focus from ordinary service delivery to the quality of service offered to their customers. Nowadays, they are many maritime seaports along the coast of East Africa; but the four that are highly competitive are Mombasa seaport in Kenya, Djibouti seaport in Djibouti, Dar es Salaam seaports in Tanzania and Maputo seaport in Mozambique [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the wealth of global and regional studies, there is a notable gap in the literature concerning a comprehensive and context-specific analysis focused on Ghana. While some studies touch on the broader West African region (Abbes, 2015;van Dyck, 2015;Abdoulkarim et al, 2019;Kalgora et al, 2019) there is a lack of in-depth examination of how seaport efficiency uniquely influences economic growth dynamics within the Ghanaian context.…”
Section: Seaport Efficiency and Economic Growthmentioning
confidence: 99%
“…Bomboma , they applied various data envelopment analysis methods such as BCC, CCR and Windows I-C methods to measure 5 key commercial seaports efficiencies in West Africa over 11 years (2005-2016). Study found that Cotonou and Abidjan seaports should regulate their operational scales in order to improve their seaport efficiency, also they found that insecurity like terrorism and outbreak disease such as Ebola impacted seaport activities in West Africa [16]. Bomboma Kalgora (2019) he used Windows I-C method of DEA model to analyse competitiveness of strategic five container seaports in West Africa covering the period of 11 years (2005-2016).…”
Section: Literature Reviewmentioning
confidence: 99%